MACHINE TRANSLATION – CAN IT ASSIST IN PROFESSIONAL TRANSLATION OF CONTRACTS? - SYCZ-OPOŃ, Joanna (Comparative Legilinguistics, 2016)
The aim of this research project is to verify whether machine translation (MT) technology can be utilized in the process of professional translation. The genre to be tested in this study is a legal contract. It is a non-literary text, with a high rate of repeatable phrases, predictable lexis, culture-bound terms and syntactically complex sentences (Šarčević 2000, Berezowski 2008). The subject of this study is MT software available on the market that supports the English-Polish language pair: Google MT and Microsoft MT. During the experiment, the process of post-editing of MT raw output was recorded and then analysed in order to retrieve the following data: (i) number of errors in MT raw output, (ii) types of errors (syntactic, grammatical, lexical) and their frequency, (iii) degree of fidelity to the original text (frequency of meaning omissions and meaning distortions), (iv) time devoted to the editing process of the MT raw output. The research results should help translators make an informed decision whether they would like to invite MT into their work environment.